2009
DOI: 10.17221/380-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction modifies morphological characteristics of seminal maize roots

Abstract: An evaluation of the effects of soil structural heterogeneity on maize (Zea mays L.) root system architecture was carried out on plants grown in boxes containing fine soil and clods. The clods were prepared at two levels of moisture (0.17 and 0.20 g/g) and bulk density (ranges 1.45-1.61 g/ml and 1.63-1.79 g/ml). Soil moisture directly affected the probability of clod penetration by maize roots. Primary roots inside the clods manifested morphological deformations in the form of bends. We observed a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…This is in agreement with [23] who noted that plant root depth and distribution in the soil is controlled by factors such as the rooting environment (soil moisture content and temperature). This is however in contradiction with findings by other researcher who found that extraction of moisture is very high when the number of plants per planting station is high resulting in faster depletion of moisture from the soil there by increasing root penetration resistance resulting in poor RLD [24]. The difference perhaps was due to the basin tillage method being used in this study which has better water retention capacity.…”
Section: Root Length Densitycontrasting
confidence: 97%
“…This is in agreement with [23] who noted that plant root depth and distribution in the soil is controlled by factors such as the rooting environment (soil moisture content and temperature). This is however in contradiction with findings by other researcher who found that extraction of moisture is very high when the number of plants per planting station is high resulting in faster depletion of moisture from the soil there by increasing root penetration resistance resulting in poor RLD [24]. The difference perhaps was due to the basin tillage method being used in this study which has better water retention capacity.…”
Section: Root Length Densitycontrasting
confidence: 97%
“…Šantrůček and Svobodová (1988) concluded that the ratio of root-branched plants was also influenced by the term of the stand establishment, stand density, and soil compaction. The effect of soil compaction on root growth within the same soil type was confirmed by Hakl et al (2007b) with lucerne and, similarly, significant relations between the bulk density and length of lateral roots or branching density was described by Konopka et al (2009) with maize roots. According to Luo et al (1995), cutting of lucerne produced an initial decrease in fine root mass followed by a recovery towards the end of the harvest cycle.…”
mentioning
confidence: 63%
“…Thus, branching density tends to decrease in the distal part of the root. The variation in branching density can also be attributed to soil factors, such as to gradients in soil bulk density (Konôpka et al, 2009), in soil moisture (Johnson and Aguirre, 1991;Ito et al, 2006), in soil temperature (Sattelmacher et al, 1990) and in soil nutrients (Gruber et al, 2013), including as roots traverse nutrient patches (Hodge, 2004;Yu et al, 2014). However, as these first-order LRs are located at different positions along the nodal roots, and the nodal roots from higher whorls exhibit steeper root angles, so that they penetrate the soil more vertically, the first-order LRs will experience a diversity of local soil environments, so being more likely to be affected by a range of soil factors.…”
Section: Discussionmentioning
confidence: 99%